Epidemiological analysis of maternal deaths in Hunan province in China between 2009 and 2014. - Xiong Lili; He Jian; Zeng Mengjun; Wu Yinglan; Xie Donghua; Wang Aihua; Kong Fanjuan; Wang Hua; Liu Zhiyu (PLoS ONE, 2018)
BACKGROUND:The control of maternal deaths continues to be a significant public health issue and commands an enormous amount of attention, especially under the future family planning policy. Here, we describe the epidemiology and trends of maternal deaths in Hunan province, and give several policy implications. METHODS:Maternal deaths in Hunan province between 2009 and 2014 were retrospectively reviewed and analyzed. Cochran-Armitage trend test was used to assess the time trends of maternal mortality rates. Binary logistic regression analyses were undertaken to identify the factors that were associated with unavoidable maternal deaths. RESULTS:In total, there were 987 maternal deaths, with the overall MMR declining by 45.24%. The most common causes of maternal death during this period were pregnancy complications (28.37%), obstetric hemorrhage (25.33%), and amniotic fluid embolism (15.70%). Obstetric hemorrhage (28.14%) was higher in rural areas, while pregnancy complications were higher (29.27%) in urban areas. In all, 627 (63.5%) deaths were avoidable. The risk factors associated with unavoidable maternal deaths was above 35 years (aOR = 1.80 95%CI: 1.27-2.55), without prenatal examination (aOR = 8.97 95%CI: 1.11-7.78), low household incomes (aOR = 1.15 95%CI: 1.02-1.29), without adopting the new way to deliver (aOR = 5.15 95%CI: 3.20-8.31), and death location (aOR = 1.09 95%CI: 1.02-1.18). The most frequent and important factors associated with avoidable deaths was improper knowledge and skills of the county medical institutions. CONCLUSIONS:Moderate progress was made in reducing the MMR in Hunan province. The government should aim to improve the basic midwifery skills in rural areas and the obstetric emergency rescue service for critically ill pregnant women in urban areas, and strengthen training to improve knowledge and skills in medical institutions in counties.